1999
DOI: 10.1002/j.2161-1882.1999.tb00140.x
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Counseling Services for Students in Academic Jeopardy: A Preliminary Study

Abstract: This study examined the impact of an academic counseling approach implemented by counseling center staff for students in academic jeopardy. Participants were 414 undergraduate students placed on academic warning and probation. Students who participated in counseling demonstrated significantly greater increases in grade point average than did students who had not received counseling.A common concern of colleges and universities is the retention of students. One segment of the student body that is at risk for at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
10
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 6 publications
1
10
0
Order By: Relevance
“…Intrusive interventions appear to increase probationary students' semester GPAs by approximately .20 (e.g., Wlazelek & Coulter, 1999) to .50 (e.g., Austin et al, 1997) on a 4-point scale. Additionally, students participating in intrusive programs may be more likely to return to good standing than nonparticipants.…”
Section: Intervention Programs For Students In Academic Jeopardymentioning
confidence: 99%
“…Intrusive interventions appear to increase probationary students' semester GPAs by approximately .20 (e.g., Wlazelek & Coulter, 1999) to .50 (e.g., Austin et al, 1997) on a 4-point scale. Additionally, students participating in intrusive programs may be more likely to return to good standing than nonparticipants.…”
Section: Intervention Programs For Students In Academic Jeopardymentioning
confidence: 99%
“…Benton, Robertson, Tseng, Newton, and Benton (2003) found that the number of students with academic problems who sought counseling at a college counseling center increased significantly over a 13-year period. In their study, Wlazelek and Coulter (1999) also found that students receiving academic counseling at a college counseling center as compared to those who did not received counseling appeared to have higher grade point averages only after one semester of receiving counseling services. Hence, Wlazelek and Coulter asserted that academic counseling interventions are instrumental in helping students.…”
mentioning
confidence: 89%
“…The critical importance of psychotherapy for students at risk of dropping out or academic dismissal has been demonstrated by Boulter (2002), Eisenberg andcolleagues (2009), Strean (1979), Wlazelek and Coulter (1999), and research shows that psychological treatment raises the likelihood of retention (Lee, Olson, Locke, Michelson, & Odes, 2009;Nelson-Field & Goodman, 2011;Sharkin, 2004;Van Brunt, 2008).…”
mentioning
confidence: 99%
“…Heisserer and Parette (2002) present a student guidance program that includes emotional support by phone conversations, and Seidman's (2005) model of attrition advocates referral to psychological consultation at professional services on and off campus. Wlazelek and Coulter (1999) describe a program in which the staff of a university's psychological services, after receiving appropriate training, provided academic counseling as well as emotional assistance to students at Downloaded by [Umeå University Library] at 02:51 03 October 2014 risk. These writers remain uncertain, however, whether therapists in general would be inclined to also provide academic guidance.…”
mentioning
confidence: 99%